Internal Control at Tax Office Pratama Madya Makassar - Nurlaelah Nurlaelah; Gery Cristyo Dalim; Siti Hajrah Salatun (Universitas 17 Agustus 1945 Semarang, 2023)
A control environment is crucial to preventing businesses at the Makassar Tax Office from committing fraud. Due to its collection of state funds and access to private taxpayer data, including financial and personal identification, it is susceptible to fraud. This study assesses the various elements of the control environment at the Makassar Intermediate Tax Service Office using the COSO Internal Control Framework, 2021 edition. A case study and a qualitative descriptive method are both used in this research. There are 85 workers in this tax office. Semi-structured interviews with twenty informants from different departments were used to gather primary data. Literature reviews, reports, regulations, and internet sources were used to gather secondary data. The use of theme analysis is one of the novel ideas in this study. 37 themes were the outcome, and these served as measurements to assess if the environmental control components were appropriate. The Makassar Intermediate Tax Service Office possesses 28 out of 37 measures, as indicated by the research findings. The findings show that working hours violations are a component of